2019
DOI: 10.1111/tbj.13154
|View full text |Cite
|
Sign up to set email alerts
|

Low risk of invasive lobular carcinoma of the breast in carriers of BRCA1 (hereditary breast and ovarian cancer) and TP53 (Li‐Fraumeni syndrome) germline mutations

Abstract: Background Invasive lobular carcinoma (ILC) of the breast has epidemiological, molecular and clinical specificities, and should likely be considered a unique entity. As for genetic susceptibility, CDH1 germline mutations predispose exclusively to ILC. Data are however scarce regarding ILC in women with BRCA1/2 (Hereditary Breast and Ovarian Cancer) and TP53 (Li‐Fraumeni syndrome) germline mutations. Methods We included all breast cancers from female patients tested at our institute between 1992 and 2016 (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In addition, the risk of ILC among carriers of PVs in other genes from multigene hereditary cancer testing panels has not been adequately defined. Some studies have reported that PVs in BRCA1 and TP53 do not predispose to ILC, 5,6 whereas PVs in BRCA2 7 and the CHEK2 I157T missense variant have been associated with ILC. [8][9][10] Furthermore, previous studies have primarily evaluated the frequency of germline PVs in CDH1 and other genes among high-risk women with family history of breast cancer or young age at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the risk of ILC among carriers of PVs in other genes from multigene hereditary cancer testing panels has not been adequately defined. Some studies have reported that PVs in BRCA1 and TP53 do not predispose to ILC, 5,6 whereas PVs in BRCA2 7 and the CHEK2 I157T missense variant have been associated with ILC. [8][9][10] Furthermore, previous studies have primarily evaluated the frequency of germline PVs in CDH1 and other genes among high-risk women with family history of breast cancer or young age at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…This almost certainly indicates that even the current reduction in score for lobular breast cancer of -2 is insufficient to reflect BRCA1 risk. The absence of an association of LBC with BRCA1 has already been noted by ourselves and others [ 6 ], with only 2/342 (0.58%) LBCs in BRCA1 breast cancer patients in one study [ 6 ]. The higher odds ratio for BRCA1 in our study is therefore likely to be explained by the strong family history of breast and/or ovarian cancer in relatives rather than a true association with BRCA1 .…”
Section: Discussionmentioning
confidence: 59%
“…This is in contrast to Petridis et al who did not identify any TP53 PGVs in an unselected series of 1434 lobular cancers [ 5 ]. A lack of association with lobular cancer and germline TP53 was also suggested by Ditchi et al in 2019 [ 6 ] but this is based on one case in only 57 carriers and the 95% CI do not exclude a 10% rate. One of our women was diagnosed with very early onset, bilateral breast cancer (the contralateral tumour was reported as invasive ductal carcinoma histologically).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…[ 21 ] 0/1434 NA NA NA Ditchi et al . [ 22 ] 1/3469 * * ILC Le AN et al . [ 23 ] 3/94 * * MDLC Kuba et al .…”
Section: Discussionmentioning
confidence: 99%